Analisis Kemampuan Vegetasi dalam Mereduksi Emisi Karbon CO2 dari Kendaraan Bermotor: Studi Kasus: Jalan Poros Kendari – Unaaha, Sulawesi Tenggara - Yudhistira, Yudhistira; Rosdiana, Rosdiana; Sakay, Ratna (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2023)
Global warming and climate change are serious challenges faced by the world today. One of the main contributors to climate change is greenhouse gas emissions, including carbon dioxide (CO2), which comes from various sources, including the transportation sector. The purpose of this study was to determine the potential of vegetation in reducing CO2 emissions from motorized vehicles on Kendari-Unaaha Road, Lalosabila Village, Wawotobi District, Konawe Regency. Data collected in the form of the number of vehicles passing through the research location for eight hours, namely at 06.00-08.00, 11.00-13.00, 16.00-18.1800 and 19.00-21.00. A counter was used to count the number of each type of vehicle passing through the study site. Individual and tree species were counted directly in the field using the census method. The amount of CO2 emissions produced by 22,427 units of motorized vehicles on the Kendari-Unaaha axis road in Lalosabila village, Wawotobi sub-district, Konawe district, Southeast Sulawesi amounted to 2495.42 kg/hour with details: Motorcycles are 556.46 kg/hour, Light vehicles are 1381.77 kg/hour, and Heavy Vehicles are 557.18 kg/hour. The results of this study show that the efficiency of CO2 absorption by vegetation is 203.91 kg/hour of total emissions of 2495.42 kg/hour with a total calculation result of 48.44 kg/hour. This shows that vegetation on the Kendari-Unaaha axis road in Lalosabila village, Wawotobi sub-district, Konawe district has not been able to reduce CO2 emissions from motorized vehicles to the maximum.